Microbiological And Physicochemical Analysis Of Water From Empurau Fish (Tor Tambroides) Farm In Kuching, Sarawak, Malaysian Borneo - Lee, Kui Soon; Lihan, S.; Ghulam Dasthagir, F.F; Mikal, K.M; Collick, F.; Ng, K.H (IJSTR, 2014)
The fish Tor tambroides locally known as empurau or kelah, is one of the most valuable and high commercial value fish species in the Cyprinidae (carps) family. The fish can grow up to the size of human in its natural habitats like cool, clean, fast moving waters and availability of riverine fruits from trees growing by the bank of upstream river. In aquaculture ponds where they are bred for the market, the fish have yet to get the right feed and appropriate water environment condition for their optimized growth, resulting in the slow production of the fish. The optimal parameter value related physicochemical and microbiological quality of water is important for the optimal growth of the fish. The Enterobacteriaceae group of bacteria has been commonly used as the main indicator for the microbiological water quality. This study aims to determine the water quality of empurau farm with regards to the physicochemical parameter value and microbiological indicator. The occurrence of Enterobacteriaceae as indicator organism and the physicochemical parameter value of the water used for the empurau farming were determined. Water samples from inlet and outlet were collected from seven empurau ponds at Indigenous Fish Research & Production Centre (IFRPC) in Tarat, Serian, Sarawak, Malaysian Borneo. Physicochemical parameters such as temperature, pH, biochemical oxygen demand (BOD), dissolved oxygen (DO) and total ammonia nitrogen (TAN) of water samples were determined. As for the microbiological analysis, water samples from the ponds were subjected to standard serial dilution followed by plating the samples on eosin methylene blue agar (EMBA) for isolation of Enterobacteriaceae. Gram staining was then performed on the isolates to determine their Gram’s characteristics. Twenty five Gram-negative isolates were further analyzed with (GTG)5-PCR to screen for clonal isolates to be used for the identification by API 20E identification system. Dendrogram constructed from the (GTG)5-PCR analysis revealed that the 25 isolates were genetically diverged resulting in 4 major clusters (G1, G2, G3, G4) and 11 sub-clusters. Based on the dendrogram, 11 representative isolates of the Enterobactericeae were selected from different clusters and these isolates were identification by API 20E kit. The result of the API 20E identification revealed that the 11 presumptive Enterobacteriaceae isolates were belonged to ten different species within nine genera of Enterobacteriaceae. The Enterobacteriaceae species confirmed were Brucella spp., Enterobacter cloacae, Citrobacter braakii, Erwinia spp., Vibrio fluvialis, Serratia odorifera, Citrobacter freundii, Butiaxella agrestis, Proteus vulgaris group and Cedecea davisae. The Enterobactericeae isolated in this study were mostly human pathogens with few fish pathogens, suggesting human activities may be affecting the water quality. Physicochemical parameters may affect the microbial population in ecology, thus indirectly affecting the development of the fish.